Efektivitas Instagram sebagai Media Komunikasi Pemasaran Agrowisata Bagus Agro Pelaga di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - KUSUMAWATI, NI KADEK AYU MARTHA; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
The Effectiveness of Instagram as Marketing Communication Media of Bagus Agro Pelaga, in Pelaga village, Petang Sub-district, Badung Regency Instagram is the most used media in marketing, one of them is to promote agrotourism. It has an impact on increasingly fierce competition for tourism industry players which requires business actors in the tourism sector to improve the quality of the media to realize sustainable tourism. The purposes of this study is to analyze the characteristics of Instagram Bagus Agro Pelaga, analyze the characteristics of Instagram users, analyze the effectiveness of Instagram as a marketing communication media, and to analyze the correlation between Instagram characteristics and the characteristics of Instagram users with effectiveness of Instagram. The data analysis method in this study used descriptive analysis and the SEM-PLS analysis technique. The results is Instagram's characteristics are classified as attractive. The characteristics of the Instagram users of Bagus Agro Pelaga are dominated by male users, the average level of education is diploma/bachelor with very low income. The effectiveness of Instagram Bagus Agro Pelaga as a marketing communication media is quite effective. The correlation between Instagram characteristics has a positive relationship and has a significant effect on the effectiveness of Instagram, while the characteristics of Instagram users have a negative relationship but have a significant effect on the effectiveness of Instagram.